Perancangan Aplikasi Flipbook Pada Erlangga Cabang Lhokseumawe - Ikhwan; Mukhtar; Bahruni (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2023)
Flipbook is an interactive digital book application utilizing three-dimensional e-book technology, allowing users to flip pages as if reading a physical book on a monitor. This technology is widely adopted by various online bookstores to engage customers. However, the Erlangga Lhokseumawe branch has not yet utilized Flipbook as part of its website strategy. This study aims to design a web-based Flipbook application to improve content quality and boost site visits. The research follows the waterfall methodology, involving stages such as literature review, data collection, system analysis, development, and testing. The Flipbook application is developed using Data Flow Diagrams (DFD) and web-based programming languages. The implementation of Flipbook facilitates the presentation of book catalogs in an informative manner and enhances visitor engagement. The findings indicate that the system optimizes digital book promotion through interactive navigation and catalog integration, offering an efficient solution for the Erlangga Lhokseumawe website.